Understanding the Characteristics of Two Different Types of Cement inRelation to the Comparison of Concrete Compressive Strength - Heri Sujatmiko (Asian Journal of Social and Humanities, 2026)
Cement is one of the main materials in construction that significantly affects the quality and compressive strength of mortar and concrete. Differences in cement characteristics, such as fineness, density, and bonding ability, may produce different compressive strength values even under the same mixture conditions. However, in practical construction work, cement selection is often based only on price and market availability without considering its technical performance. Therefore, this study aimed to compare the characteristics and compressive strength of mortar produced using Puger cement and Gresik cement under identical mixture proportions and curing conditions. This research employed an experimental quantitative method conducted in the Civil Engineering Laboratory. Mortar specimens were prepared using mixture proportions of 1:3, 1:4, 1:5, and 1:6 with Lumajang sand as fine aggregate. Compressive strength testing was performed at curing ages of 14, 21, and 28 days. The results showed that mortar compressive strength increased with curing age, while higher sand composition reduced strength performance. Gresik cement consistently produced higher compressive strength than Puger cement in all mixture variations. The highest compressive strength at 28 days was achieved by Gresik cement with a 1:3 mixture proportion at 197.13 Kg/cm². In conclusion, cement type significantly influences mortar compressive strength and should be carefully considered in construction material selection to achieve optimal structural quality and cost efficiency.